An alternative aerodynamic mitigation measure for improving bridge flutter and vortex induced vibration (VIV) stability: Sealed traffic barrier. Issue 206 (November 2020) - Bai, Hua; Ji, Naichuan; Xu, Guoji; Li, Jiawu
Abstract: This study proposes an alternative aerodynamic mitigation measure, i.e., sealed traffic barrier, for bridges and verifies its efficacy in improving the flutter and vortex induced vibration (VIV) stability of bridges through wind tunnel tests for three distinctive real-world bridge projects. The results show that: (1) The measure of the sealed traffic barrier with regular intervals along the bridge deck has a significant influence on the flutter and VIV performance of the bridge. Thus, a reasonable design of the traffic barrier can simultaneously improve the bridge's flutter and VIV stability; (2) The sealed traffic barrier with vertical intervals along the bridge can effectively suppress the vertical VIVs of the bridge, while the sealed traffic barrier without vertical intervals, i.e., configured continuously along the bridge, has a better vibration suppression effect on the torsional VIV than that on the vertical VIV; (3) This proposed measure installed on both sides of the bridge deck imposes favorable suppression effect for the flutter vibration, similar to the upward central stabilizer. In case with the sealing form fixed, but a reduced height, for the barrier, the flutter stability at different wind attack angles is slightly decreased; and (4) In certain scenarios, increasing the ventilation rate of the traffic barrier results in an increase for the flutter critical wind speed at positive wind attack angles, but a decrease for the flutter critical wind speed at negative wind attack angles. This aerodynamic mitigation measure has been successfully applied to more than ten other bridge projects based on the wind tunnel tests by the leading authors, offering a reliable approach in improving both flutter and VIV for bridges. Highlights: An alternative aerodynamic mitigation measure of the sealed traffic barrier is proposed. Its efficacy in improving the bridge flutter and VIV performance has been verified through wind tunnel tests. It has been successfully applied to many bridge projects based on wind tunnel tests.